Yangzhu – enfant terrible filosfskega daoizma (Филолошки студии, 2019)
Yang Zhu, a Chinese philosophers from the 4th Century BC, has been in the history of Chinese philosophy regarded as a selfish hedonist, unable of virtuous life in community, structured in accordance with rigid Confucian philosophy. As such, the official Confucian historiography has always marked him as a heretic thinker, unworthy of being a real philosopher. The present article tries to reject such an interpretation of Yang Zhu's philosophy and to expose the fact, that his opus should be regarded as an extraordinarily egalitarian philosophy, striking for freedom, dignity and personal integrity of every individual in society. The article follows the presumption, according to which Yang Zhu is the very representative of classical Daoism, who tried in his work to consistently realize the principle of social tolerance, autonomy and individual freedom in the sense of »to live and to let live«.